The Extent Of Commitment Of Industrial Companies To The Dimensions Of Sustainable Development A Field Study At Joud For Household Electrical Industries - Haddad, Khaldon Ahmad (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to determine the extent of Joud Household Electrical appliances commitment to the dimensions of sustainable development: economic, social and environmental. The research was based on the descriptive analytical approach, and the research community included all employees of Joud Electrical Appliances Company, and the questionnaire was relied upon as a tool to collect information, where (120) questionnaires were distributed, and (113) questionnaires valid for statistical analysis were retrieved. The results showed that Jawd Household Electrical Appliances adheres to the dimensions of sustainable development, and is of relative importance (75.04%), where the commitment to the social dimension came first, followed by the commitment to the environmental dimension, and finally the commitment to the economic dimension. هدف البحث إلى تحديد مدى التزام شركة جود للأدوات المنزلية الكهربائية بأبعاد التنمية المستدامة: الاقتصادي والاجتماعي والبيئي. اعتمد البحث على المنهج الوصفي التحليلي وشمل مجتمع البحث جميع العاملين في شركة جود للأدوات المنزلية الكهربائية, وتمّ الاعتماد على الاستبانة كأداة لجمع المعلومات, حيث تمّ توزيع (120) استبانة, وتمّ استرجاع (113) استبانة صالحة للتحليل الإحصائي. أظهرت النتائج أنّ شركة جود للأدوات المنزلية الكهربائية تلتزم بأبعاد التنمية المستدامة, وبأهمية نسبية (75.04%), حيث جاء الالتزام بالبعد الاجتماعي بالمرتبة الأولى, يليه الالتزام بالبعد البيئي, وأخيراً الالتزام بالبعد الاقتصادي.